Curing Characteristics And Properties Of Epoxidized Natural Rubber ( ENR ) - Amin, Md. Sadequl (1997)

(untitled)
The cure characteristics of accelerated sulphur vulcanization of epoxidized natural rubber containing 25 mol % of epoxidation ( ENR 25 ) was studied while one grade of unmodified natural rubber - standard Malaysian rubber light ( SMR L ) was used as a control. The influences of different accelerator types - zinc dimethyldithiocarbamate ( ZDMC ), tetramethylthiuram disulphide (TMTD), diphenylguanidine ( DPG ), N-t-butylbenzothiazole-2-sulphenamide (TBBS ), and 2-mercaptobenzothiazole ( MBT ) at various temperatures were investigated. Three vUlcanization systems - conventional high-sulphur vulcanization ( CV ), semi-efficient vulcanization ( semi-EV ) and efficient vUlcanization ( EV ) were also investigated. Mooney Shearing Disk Viscometer ( MV 2000 ) and Moving Die Rheometer ( MDR 2000 ) were used to determine the Mooney scorch time and cure time respectively in the temperature range of 100 to 180 DC. Sifat-sifat pematangan· bagi pemvulkanan getah asli terpoksida yang mengandungi 25 % mol pengepoksidaan ( ENR 25 ) terpecut sulfur telah dikaji sementara getah asli ( SMR L ) telah digunakan sebagai kawalan. Kesan berbagai pemecut - zink dimetilditiokarbamat ( ZDMC ), tetrametiltiuram disulfida (TMTD ), difenilguanidin DPG), N-tbutilbenzotiazol- 2-sulfenamida ( TBBS ) dan 2-merkaptobenzotiazol ( MBT ) pada suhu yang berlainan dikaji. Tiga jenis sistem pemvulkanan - pemvulkanan konvensional bersulfur tinggi (CV ), pemvulkanan semi-efektif ( semi-EV) dan pemvulkanan efektif ( EV ) juga telah dikaji. Mooney Shearing Disk Rheometer ( MV 2000 ) dan Moving Die Rheometer ( MDR 2000 ) masing-masing telah digunakan untuk menentukan masa skorj Mooney dan masa pematangan di dalam julat suhu 1 aaoc hingga 180c.